FACTORS AFFECTING COMPANY VALUE WITH CSR AS A MODERATING VARIABLE IN ENERGY SECTOR COMPANIES - Frans Tegas; Susanto Salim (International Journal of Application on Economics and Business, 2024)
This study’s research targeted to determine how profitability, leverage, and liquidity affected a company’s value while using Corporate Social Responsibility as a moderating variable. The 17 energy sector companies used in this study serve as examples for the years 2021-2022. This study uses multiple linear regression analysis with the SPSS program for hypothesis testing. This study concludes that while profitability and leverage have a significant positive effect on a company’s value, liquidity does not affect that value. However, Corporate Social Responsibility disclosure can moderate the impact of leverage and profitability on a company’s value.